Increased risk of wheeze and decreased lung function after respiratory syncytial virus infection. - Kim Zomer-Kooijker (PLoS ONE, 2014)
BACKGROUND: A relationship between hospitalization for respiratory syncytial virus (RSV) bronchiolitis and asthma development has been suggested in case-control studies. OBJECTIVE: The aim of this study was to assess the risk of current wheeze, asthma, and lung function at school age in infants previously hospitalized for RSV bronchiolitis compared to non-hospitalized children. METHODS: For this study, data from a prospective birth cohort of unselected, term-born infants (n = 553), of whom 4 (0.7%) were hospitalized for RSV bronchiolitis, and a prospective patient cohort of 155 term infants hospitalized for RSV bronchiolitis were used. Respiratory outcomes at age 6 in children hospitalized for RSV bronchiolitis were compared to non-hospitalized children. RESULTS: The risk of current wheeze was higher in hospitalized patients (n = 159) compared to non-hospitalized children (n = 549) (adjusted odds ratio (OR) 3.2 (95% CI 1.2-8.1). Similarly, the risk of current asthma, defined as a doctor's diagnosis of asthma plus current symptoms or medication use, was higher in hospitalized patients (adjusted OR 3.1 (95% CI 1.3-7.5). Compared to non-hospitalized children, RSV bronchiolitis hospitalization was associated with lower lung function (mean difference FEV1% predicted -6.8 l (95% CI (-10.2 to -3.4). CONCLUSIONS AND CLINICAL RELEVANCE: This is the first study showing that hospitalization for RSV bronchiolitis during infancy is associated with increased risk of wheezing, current asthma, and impaired lung function as compared to an unselected birth cohort at age 6.